Categorizing Collective Capabilities - Rosignoli, Francesca (PARTECIPAZIONE E CONFLITTO, 2019)
In recent years, a growing body of literature has started to take up the issue of collectivity within the capability approach, by particularly examining the notion of collective capabilities, the reasons for using this concept, its critiques and limitations. However, a proper categorization of collective capabilities aiming at defining which types of capabilities actually are, is rarely studied. The goal of this contribution is to fill such gap by categorizing collective capabilities as well as providing a specific list of collective combined capabilities. The list includes two collective capabilities: the 'resistant capability' and the 'resilient capability'. After having briefly outlined the most recent contributions of the capability theorists for including the issue of the collectivity within the Capability Approach (CA), I then proceed as follows. First, I examine what collective capabilities are and why they matter for the CA. Second, I provide a categorization of collective capabilities based on the ontological difference between collective and individual capabilities. Third, the resulting extension of Nussbaum's version of the CA is carried out by including a specific list for collective combined capabilities. Finally, I investigate how this extension affects Nussbaum's CA.